Apophis: May a meteor activity happen on Earth after the 2029 closest approach? - Valvano, G. [UNESP]; Sfair, R. [UNESP]; Winter, O. C. [UNESP]; Machado-Oliveira, R. [UNESP]; Borderes-Motta, G. (Oxford University Press (OUP), 2024)
The potentially hazardous asteroid 99942 Apophis will have a very close approach to the Earth in 2029. The encounter on its own may provide measurements of Earth's effects on Apophis' surface and also contribute to the improvement of some physical characteristics of the asteroid. In a previous work, we assumed the existence of a hypothetical disc of particles around Apophis before the 2029 encounter, and identified the particles that would escape from the gravity domain of Apophis due to the Earth's gravitational perturbation during the close encounter. In the current work, we investigate the possibility of a meteor activity originating from this event. We study the orbital evolution of these particles computing the MOIDs of the particles with respect to the Earth for the following 200 yr. Our results are not favourable for a meteor activity on Earth. However, a meteoroid activity on the Moon might happen during the encircling period after 88 yr of the 2029 encounter.
Keywords: celestial mechanics; minor planets, asteroids: general; planetary systems; planets and satellites: dynamical evolution and stability